Ortho-phthalaldehyde-induced skin mucous membrane damage from inadequate washing. (2nd February 2011) - Horikiri, Masaru; Park, Susam; Matsui, Takahiro; Suzuki, Komei; Matsuoka, Takanori
Abstract : Because body fluids and blood have a tendency to adhere to transesophageal echo devices, a high level of sterilisation is required when cleaning them. Ortho-phthalaldehyde (OPA) has been widely used in Japan since being approved as a high-level sterilant. The authors report a patient with widespread, severe skin and mucous membrane damage of the lip, tongue, pharynx and oesophagus areas that was attributed to inadequate washing after the sterilisation of a transesophageal echo device with OPA. This patient experienced sequelae, which did not improve after more than 1 year of continuous treatment. When using medical devices sterilised with OPA, the use of a probe cover, when applicable, is recommended and complete washing prior to use is required.